In vivo screening of flavonoid compounds revealed quercetin as a potential drug to improve recovery of angiostrongyliasis after albendazole treatment - Lam, Ho Yin Pekkle; Huang, Yu-Ting; Liang, Ting-Ruei; Peng, Shih-Yi (PLOS Neglected Tropical Diseases, 2024)
Human angiostrongyliasis, caused by consuming the larva stage of Angiostrongylus cantonensis, is an infectious disease involving the central nervous system (CNS) and ophthalmic system. Current treatment of angiostrongyliasis involves albendazole accompanied by analgesics and corticosteroids. However, long-term use of corticosteroids may lead to significant adverse effects. In the current study, we screened through different potentially effective flavonoid compounds and identified quercetin as an effective anti-inflammatory agent in an angiostrongyliasis mouse model. Our results identified that quercetin may reverse the neurological defects in mice with angiostrongyliasis. The brain pathology and inflammatory status were also improved by albendazole-quercetin co-therapy. Further analysis showed that albendazole-quercetin co-therapy had a better therapeutic effect than albendazole or quercetin monotherapy. This therapeutic effect was achieved by inhibiting the brain inflammasome activation and apoptosis. Albendazole-quercetin co-therapy also leads to the inhibition of brain IL-5, possibly leading to improved pathology. Our results here proved that quercetin may serve as a potential adjuvant drug in treating human angiostrongyliasis.